Methods and Means of public relation in dealing with Bureaucracy - Nzar Kamel, Noor; Musa Jasim, Baqir (ALBAHITH ALALAMI, 2021)
The importance of Public Relations activity has increased during the last half of the last century as a specialized and modern administrative function in most institutions. It has, moreover, become an integral part of activities of those institutions of various types, due to its pivotal role in building its reputation and drawing a good mental image among its audiences, as well as its influential and basic role in maintaining communication and the communication between its members at its various levels and their job tasks to ensure the greatest amount of understanding and to enhance trust between them. This is why public relations activity has become indispensable in all institutions, and without it, it is difficult to achieve any coordination activity or interactive relations. Public Relations was, in addition, able to impose itself as part of its administrative activity, which greatly contributes to measuring the public’s attitudes and knowing their desires to include them in the its administrative curriculum in order to gain the public confidence that leads to build a positive impression.As for the administrative system in the institution, it is the executive body concerned with achieving its goals, measuring the extent of its progress and developing that institution through the distribution of tasks, responsibilities and powers. Yet, every executive work has obstacles and problems that appear during implementing the plan stages that prevent the progress of work according to the specified times or the desired quality of that work.Among the most important of these administrative bureaucratic obstacles that have leadership and the largest portion of interest in modern administrative thought for their great influence in determining the success of institutions